Excess Sensitivity and Volatility of Long Interest Rates: The Role of Limited Information in Bond Markets - Meredith Beechey (Sveriges Riksbank, 2004)
Asymmetric information between the central bank and bond markets creates an inference problem that affects the behaviour of long interest rates. This paper employs a simple macroeconomic model with a time-varying infation target to illustrate the implications of asymmetry for the sensitivity of long rates and volatility of bond returns. When the central bank's infation target is not communicated and macroeconomic shocks are imperfectly observed, bond markets infer the value of the target from noisy signals. This heightens the sensitivity of long-run infation expectations to transitory shocks, thereby raising the measured reaction of long rates to monetary policy and to infation surprises. Calibrated coe±cients from such regressions are more than twice as large when bond markets lack knowledge of the target compared with a full information scenario. Time variation in the infation target is the main source of volatility, but learning adds to the ability of the model to explain the observed volatility of returns along the yield curve.
Keywords: E43; E52; 330; Term structure of interest rates; yield curve; limited information; learning; excess sensitivity; excess volatility.